Automation of measurement of the bandwidth of radiation - Ільницький, Л. Я.; Сібрук, Л. В.; Сугоняк, З. В. (Proceedings of National Aviation University (archive), 2021)
The structural scheme of an automatic measuring device for estimating the width of the occupied band according to the definition of the International Radio Consultative Committee is proposed. The scheme uses two identical filters of the lower or upper frequencies and two frequency converters. The feedback circuits provide the automatic determination of the bandwidth of the test signal. The sources of errors related to the character of the investigated signals (radiation class), with the electromagnetic environment and the hardware implementation of the principle of action are determined.